Decreased Cerebral Blood Flow and Delayed Arterial Transit Are Independently Associated With White Matter Hyperintensity - Zhang, Ruiting; Huang, Peiyu; Wang, Shuyue; Jiaerken, Yeerfan; Hong, Hui; Zhang, Yao; Yu, Xinfeng; Lou, Min; Zhang, Minming (Frontiers in Aging Neuroscience, 2022)
Aim- White matter hyperintensities (WMH) and lacunes were important features of cerebral small vessel disease (CSVD), which contributes to 25% of ischemic strokes and 45% of dementias. Currently, the underlying mechanisms of WMH and lacunes were not clear, and the role of hemodynamic changes are not fully investigated. In this study, we aimed to measure the cerebral blood flow (CBF) and arterial transit in CSVD patients, and to investigate their association with WMH and lacunes. Methods- We retrospectively analyzed the prospectively collected database of CSVD patients. Ninety-two CSVD patients with complete imaging data were included. We used arterial spin labeling (ASL) with post labeling delay time (PLD) of 1525ms and 2025ms to measure CBF respectively, and the difference between CBFPLD1.5 and CBFPLD2.0 were recorded as δCBF. We performed regression analysis to understand the contribution of CBF, δCBF to CSVD imaging markers. Results- We found that CBF derived from both PLDs were associated with WMH volume and the presence of lacune. CBFPLD1.5 was significantly lower than CBFPLD2.0 in CSVD patients, and δCBF was correlated with WMH volume but not the presence of lacune. Furthermore, CBFPLD2.0 and δCBF were both associated with WMH in multiple regression analysis, suggesting an independent effect of delayed arterial transit. On an exploratory basis, we investigated the relationship between venous disruption on δCBF, and we found that δCBF correlated with deep medullary veins score. Conclusion- Both CBF and arterial transit were associated with WMH. ASL with multiple PLDs could provide additional hemodynamic information to CSVD related studies.